The Role of Arabic Calligraphy in Shaping the Religious Character Students: A Literature Review of Islamic Education - Fatihatus Sya'adah; Nyayu Soraya; Baldi Anggara (FKIP - Universitas Riau, 2026)
This study analyzes the role of Arabic calligraphy in shaping the religious character of students in Islamic education. However, schools still face many challenges in implementing it. These include a lack of learning media that evenly touch on cognitive, affective, and psychomotor aspects. One very beneficial option is the use of Arabic calligraphy as an educational tool. The purpose of this study is to evaluate the role of Arabic calligraphy in shaping students religious character. A literature review method was used to collect data from various relevant scientific sources, including books, journals, and previous research results. The results showed that through the process of writing, decorating, and appreciating verses from the Qur'an, Arabic calligraphy plays a strategic role in enhancing religious values. This process involves cognitive, affective, and psychomotor aspects simultaneouslyThis study found that the use of local arts and culture, especially Arabic calligraphy, can be a useful and contextual alternative method to strengthen the formation of students religious character.